Health and Voting in Rural America - Cahill, Katie A.; Ojeda, Christopher (Frontiers in Political Science, 2021)
This research explores the impact of health on political behavior, with the goal of uncovering important variation in the dynamics of civic participation in rural communities. Drawing on the results of county and individual-level analyses, including novel survey data from an Appalachian community, these analyses indicate that health matters less for rural voters. Models using county-level data indicate that poor health is significantly and negatively related to voter participation across counties, even when controlling for educational attainment, poverty, diversity, and political competition. However, health loses its explanatory power in rural counties once a control for religiosity is introduced. Health is also less important predictor in rural places where there is a high cost-of-voting, a finding counter to the notion that high costs would uniformly amplify the negative effects of health disparities. Importantly, the individual-level model provides additional support for many of these findings, as well as new insights into the complexity of rural political behavior. This study suggests that place has an important role in understanding the political behavior of American voters and requires more expansive consideration in future research.